UJI EFEK AFRODISIAKA DARI EKSTRAK BAWANG PUTIH (Allium sativum) PADA HEWAN COBA MENCIT (Mus musculus) - Maulita Indrisari; St. Rahimah; Abd Halim Umar; Ade Putri Allyah (Universitas Islam Negeri Alauddin Makassar, 2016)
Garlic (Allium sativum) empirically used as a stamina enhancer, potentially as afrodisiaka. The purpose of this study was to determine whether the ethanol extract of the garlic effect as an aphrodisiac in male mice as animals models and used ICC (Introducing, Climbing, and Coitus) as parameters by treated with Garlic extracted Garlic was extracted by maceration with ethanol 70 %. Animal tests were used 15 male mice and 15 famale mice were divided into five treatment groups. Each group consists of 3 males and 3 females. The first group was given with Na.CMC 1 % as a negative control, the second group was given Pasak bumi as a positive control, a group III were given ethanol extract of garlic 150 mg/kgBB, group IV were given ethanol extrac of garlic 200 mg/kgBB and group 5 was given ethanol of the garlic 300 mg/kg BB.As The results showed ethanol extract of the garlic 300 Mg/Kg BB can act as aphrodisiac in experimental animals male mice (Mus musculus).